2014
DOI: 10.1128/jvi.02526-13
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of H2N2 Influenza Viruses from the Avian Reservoir

Abstract: H2N2 influenza A viruses were the cause of the 1957-1958 pandemic. Historical evidence demonstrates they arose from avian virus ancestors, and while the H2N2 subtype has disappeared from humans, it persists in wild and domestic birds. Reemergence of H2N2 in humans is a significant threat due to the absence of humoral immunity in individuals under the age of 50. Thus, examination of these viruses, particularly those from the avian reservoir, must be addressed through surveillance, characterization, and antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 51 publications
(60 reference statements)
1
49
0
1
Order By: Relevance
“…After 21 days, blood was collected to test for seroconversion by HI assay with turkey red blood cells 37, 38. The HI assay was conducted in triplicate, and the titers are reported as the geometric means.…”
Section: Methodsmentioning
confidence: 99%
“…After 21 days, blood was collected to test for seroconversion by HI assay with turkey red blood cells 37, 38. The HI assay was conducted in triplicate, and the titers are reported as the geometric means.…”
Section: Methodsmentioning
confidence: 99%
“…This virus caused disease in mice and pigs following intranasal inoculation (7)(8)(9), and characterization of several additional avian H2N2 viruses demonstrated that many isolates could replicate in mice and in human bronchial epithelial cells (9,10). In contact transmission studies, both avian H2 and swine H2N3 viruses transmitted efficiently in ferrets, and sequence analysis indicated that these viruses rapidly acquire mutations in the hemagglutinin (HA) receptor-binding site (7,11).…”
mentioning
confidence: 99%
“…Jones et al (35) provided a comprehensive risk assessment for the potential reintroduction in humans of H2N2 viruses currently circulating in wild birds and found that while the risk was low, these viruses exhibited pathogenicity, replicative competency, and direct-contact transmission in experimental mammalian systems. Moreover, a lack of sustained systematic global influenza surveillance in birds and other animals severely limits the power of any risk assessment.…”
mentioning
confidence: 99%